2010 Sixth International Conference on Natural Computation 2010
DOI: 10.1109/icnc.2010.5582616
|View full text |Cite
|
Sign up to set email alerts
|

Fast decryption utilizing correlation calculation for BSS-based speech encryption system

Abstract: Original BSS (blind source separation)-based speech encryption system utilizes BSS to perform decryption, but the complexity of BSS algorithms limits the decryption speed and its real-time application. Correlation calculation is an algebraic decryption method originally proposed for BSS-based image cryptosystem to overcome two limitations of BSS: permutation and scaling ambiguity and difficulty for separating strongly correlated images. Considering that there is similarity between encryption matrix for speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Once the mixture signals x ( t ) = [ x 1 ( t ), x 2 ( t ),…, x p ( t )] T are received, the key signals I are regenerated by the secret seed I 0 and the key signals II are produced by the chaotic system using the initial conditions. Usually, BSS is then performed [ 2 , 17 ] to recover original signals. But in this paper, we employ approximate calculation to recover original signals.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Once the mixture signals x ( t ) = [ x 1 ( t ), x 2 ( t ),…, x p ( t )] T are received, the key signals I are regenerated by the secret seed I 0 and the key signals II are produced by the chaotic system using the initial conditions. Usually, BSS is then performed [ 2 , 17 ] to recover original signals. But in this paper, we employ approximate calculation to recover original signals.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The paper analyzed the correlation of speech signals with key signals, and then utilized the correlation calculation to achieve speech decryption. The experiment results showed that correlation calculation decryption nicely simplifies BSS-bsed speech encryption system, largely speeds up the speech decryption, and slightly improves the quality of decrypted speech signals (Guo & Lin, 2010). While Mermoul and Belouchhrani claimed that the interactability of the under-determined BSS problem has been used for the proposal of BSS-based speech encryption has some weakness from cryptographic point of view.…”
Section: Introductionmentioning
confidence: 99%